2018
DOI: 10.1017/s0144686x1800096x
|View full text |Cite
|
Sign up to set email alerts
|

Should I've stayed or should I've gone? What residents of continuing care retirement communities and former candidates think and feel one year after their decision: a quantitative longitudinal comparison

Abstract: The aim of this study was to compare satisfaction with residence, wellbeing and physical health of continuing care retirement community (CCRC) residents with people who considered enrolling in the same CCRCs but elected not to move. A total of 101 participants were recruited from 13 CCRCs located in multiple cities in the United States of America. A phone interview was conducted with participants three months or less from enrolment and one year later. Compared with those who chose not to move, CCRC residents r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…As mentioned earlier, resident satisfaction, as a research topic, has been investigated in the senior living context by several previous researchers (Cutchin et al , 2010; Green et al , 2020; Lee, 2020a). However, only a limited number of CCRC attributes or characteristics have been studied as the antecedents of resident satisfaction (Goh et al , 2013; Nichols, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned earlier, resident satisfaction, as a research topic, has been investigated in the senior living context by several previous researchers (Cutchin et al , 2010; Green et al , 2020; Lee, 2020a). However, only a limited number of CCRC attributes or characteristics have been studied as the antecedents of resident satisfaction (Goh et al , 2013; Nichols, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Resident satisfaction can be defined as residents’ positive evaluation of CCRC attributes. Prior literature posited that seniors were generally satisfied with their relocation to CCRCs (Green et al , 2020; Marx et al , 2011). Although some studies indicated that food service played an essential role in resident satisfaction (Curtis et al , 2005; Goh et al , 2013; Seo and Shanklin, 2005, 2007), other studies discovered that the social environment in CCRCs was more important than the physical environment in affecting resident satisfaction (Cutchin, 2010; Erickson and Krout, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation